2020
DOI: 10.3389/fnins.2020.00811
|View full text |Cite|
|
Sign up to set email alerts
|

Lysophosphatidic Acid Receptor 1 Specifically Labels Seizure-Induced Hippocampal Reactive Neural Stem Cells and Regulates Their Division

Abstract: A population of neural stem cells (NSCs) dwelling in the dentate gyrus (DG) is able to generate neurons throughout adult life in the hippocampus of most mammals. These NSCs generate also astrocytes naturally and are capable of generating oligodendrocytes after gene manipulation. It has been more recently shown that adult hippocampal NSCs after epileptic seizures as well as subventricular zone NSCs after stroke can give rise to reactive astrocytes (RAs). In the hippocampus, the induction of seizures triggers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…13 The effects of LPA are mediated through 6 distinct LPA receptors (LPARs), termed LPA 1 -LPA 6 (gene names Lpar1-Lpar6), which activate major cellular signaling pathways, including the Wnt, phosphoinositide 3-kinase (PI3K), and epidermal growth factor (EGF) pathways. 13 The expression of LPAR in embryonic stem cells 14,15 and neural stem cells, 16,17 along with the effects of LPA on neural development 18 and myeloid differentiation, 19 has been reported. A recent study using mouse enteroids showed that LPA can be used instead of EGF to support enteroid growth.…”
mentioning
confidence: 99%
“…13 The effects of LPA are mediated through 6 distinct LPA receptors (LPARs), termed LPA 1 -LPA 6 (gene names Lpar1-Lpar6), which activate major cellular signaling pathways, including the Wnt, phosphoinositide 3-kinase (PI3K), and epidermal growth factor (EGF) pathways. 13 The expression of LPAR in embryonic stem cells 14,15 and neural stem cells, 16,17 along with the effects of LPA on neural development 18 and myeloid differentiation, 19 has been reported. A recent study using mouse enteroids showed that LPA can be used instead of EGF to support enteroid growth.…”
mentioning
confidence: 99%
“…The reactive astrocyte-like morphology typical of the seizure-induced React-NSCs (Sierra et al, 2015b; Muro-García et al, 2019; Valcárcel-Martín et al, 2020) was reduced and NSCs looked closer to normal conserving their radial morphology in the MTLE-HS mice treated with gefitinib. To quantify this effect, we analyzed Nestin-GFP+ cells by Sholl analysis and measured the overall process length, the cell volume and ramification as branch points (Figure 3F, 3G and 3H, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In parallel to alterations in neurogenesis, seizures trigger astrogliogenesis in the DG. We have recently characterized using mouse models of MTLE-HS, how seizures induce the transformation of hippocampal NSCs into reactive NSCs (React-NSCs) who contribute to HS through the direct generation of reactive astrocytes at the expense of neurogenesis (Sierra et al, 2015a; Muro-García et al, 2019; Valcárcel-Martín et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…NSPCs can be isolated from the adult hippocampal DG taking advantage of LPA 1 -GFP transgenic mice, yet only a subset of the precursors are proliferative cells based on the surface expression of other markers such as EGFR and Prominin-1. The remainder (majority) of LPA 1 -GFP are classified as nonproliferative or quiescent precursor cells (Walker et al, 2016;Valcárcel-Martín et al, 2020), so it is tempting to speculate that LEF1 may be involved in maintaining the expression of Lpar1 in quiescent NSPCs. Finally, it is worth to note that the Martynoga et al (2013) study (on which the analysis of LEF1 binding sites in enhancers is based) was performed in mouse NSPCs expanded in FGF2 and EGF, while our study employed rat NSPCs expanded in FGF2 only.…”
Section: Discussionmentioning
confidence: 99%